Amyloid tumour of the colon. Issue 6 (June 1995) - Deans, G T; Hale, R J; McMahon, R F; Brough, W A
Abstract : A case of amyloid tumour of the colon and the first in association with a carcinoma is reported. A previously healthy 65 year old man presented with non-specific symptoms of lower abdominal pain and flatulence without rectal bleeding. A clinical diagnosis of diverticular disease was made and colonoscopy performed. Two lesions (one at 15 cm and the other at 30 cm from the anal margin) were found on endoscopy and removed. On histology, the lesion at 15 cm was a moderately differentiated adenocarcinoma and that at 30 cm contained amyloid. Further tests (standard tinctorial methods and immunohistochemistry) revealed the 30 cm lesion to be an amyloid tumour of the colon of AL (lambda) type. When biopsy of an atypical, large, solitary colorectal lesion reveals amyloid deposition, the possibility of an amyloid tumour should be considered and the lesion resected.